Sudden Infant Death Syndrome-Associated Mutations in the Sodium Channel Beta Subunits - Tan, Bi-Hua (2010)
BACKGROUND: Approximately 10% of sudden infant death syndrome (SIDS) may stem from potentially lethal cardiac channelopathies, with approximately half of channelopathic SIDS involving the Na(V)1.5 cardiac sodium channel. Recently, Na(V) beta subunits have been implicated in various cardiac arrhythmias. Thus, the four genes encoding Na(V) beta subunits represent plausible candidate genes for SIDS. OBJECTIVE: To determine the spectrum, prevalence and functional consequences of sodium channel beta subunit mutations in a SIDS cohort. METHODS: In this IRB-approved study, mutational analysis of the 4 beta subunit genes: SCN1B – 4B was performed using PCR, DHPLC, and direct DNA sequencing of DNA derived from 292 SIDS cases. Engineered mutations were co-expressed with SCN5A in HEK 293 cells, and whole cell patch clamped. One of the putative SIDS-associated mutations was similarly studied in adenovirally transduced adult rat ventricular myocytes. RESULTS: 3 rare (absent in 200–800 reference alleles) missense mutations (β3-V36M, β3-V54G and β4-S206L) were identified in 3/292 SIDS cases. Compared to SCN5A+β3-WT, β3-V36M significantly decreased peak I(Na) and increased late I(Na) while β3-V54G resulted in a marked loss-of-function. β4-S206L accentuated late I(Na) and positively shifted the midpoint of inactivation compared to SCN5A+β4-WT. In native cardiomyocytes, β4-S206L accentuated late I(Na) and increased the ventricular action potential duration (APD) compared to β4-WT. CONCLUSION: This study provides the first molecular and functional evidence to implicate the Na(V) beta subunits in SIDS pathogenesis. Altered Na(V)1.5 sodium channel function due to beta subunit mutations may account for the molecular pathogenic mechanism underlying approximately 1% of SIDS.